PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN YANG TERCATAT DI INDEKS KOMPAS 100 BURSA EFEK INDONESIA TAHUN 2013-2015 - Qifari Gisriana; Msy. Mikial; Muhammad Hidayat (Jurnal Ilmiah Ekonomi Global Masa Kini)
This examination is intended to test the impact of Intellectual Capital against companies that were included in the Kompas 100 Index in Indonesia stock exchange (BEI) 2013-2015. Dependent variable in this examination is Return on Assets (ROA). The independent variables in this examination contain Capital Employed, Human Capital, and Structural Capital. Researcher obtains the data by observing the annual reports and financial reports of these company by the internet (website http://www.idx.co.id). The population in this research are companies that were included in the Kompas 100 Index in Indonesia stock exchange (BEI) 2013-2015. The sample was selected using purposive sampling method and obtained 34 companies being sampled, so it becomes 102 data. Analytical techniques used is multiple regression analysis.The result of the examination shows that not all independent variables have an effect on firm’s performance. Simultaneously, all independent variables have significant effects. But partially, only Capital Employed which has significant effect on Return on Assets. Other while, Human Capital and Structural Capital do not have.Kewords:intellectual capital, capital employed, human capital, structural capital, ROA